Is Generating Renewable Energy a Religious Use of Property? A Question as Congregations Implement Community Solar Programs - Bolgiano, William (Columbia Journal of Environmental Law, 2019)
“Community solar,” a method for financing local solar energy projects, has recently gained a foothold in many states. It is a promising method of promoting both renewable energy and distributed generation. Religious congregations are often uniquely able and motivated to implement these projects to realize the direct benefits of the infrastructure investment and a reduced carbon footprint, as well as the indirect benefits that derive from the concerted action of an ethically motivated community. In fact, local community solar implementation by established and well regarded institutions, as religious congregations often are, may inspire congregants and other community members to do the same, or to support public policy measures aimed at expanding renewable energy. A potential problem arises when congregations use their tax-exempt property (such as church rooves) to host community solar projects: how does a community solar project fit within the limited uses allowed under the tax-exempt status of a religious institution? If religious congregations use their tax-exempt property to generate renewable energy for off-site uses, these organizations may lose their tax-exempt status. In Part II, this Note details the tax treatment of religious institutions. Part III sets forth the benefits of and different models for community solar. Part IV explores the unique opportunity community solar presents for religious congregations. Part V details the tax exemption obstacle facing such projects, and selected state approaches. Part V then identifies three strategies religious congregations can deploy to ensure that solar projects remain consistent with religious uses of property for tax exemption purposes. First, congregations should eschew financial profits in community solar project structures. Second, the projects should incorporate traditional charitable activities such as youth education and economic justice. And third, congregations should clearly integrate solar projects into their religious activities.